Dakwah Tanpa Tarif: Transformasi Spiritual Komunitas Pendakwah Keren melalui Filosofi 'Ikhlas Ruhnya Dakwah' di Sulawesi Selatan - Rachmat Hidayat; Hidayat, Rachmat; Mahmuddin; Firdaus Muhammad (Lentera Jurnal, 2025)
This study aims to analyze the da'wah strategy of the Pendakwah Keren Community (KPK) through the slogan "Ikhlas Ruhnya Dakwah" (Sincerity is the Spirit of Da'wah) in South Sulawesi. The focus of this study is on how this community interprets and implements the value of sincerity as the spirit of da'wah in its activities, and how this strategy shapes a positive image in the eyes of the community. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, participatory observation, and documentation of KPK activities in various regions in South Sulawesi. The results show that the KPK implements six main strategic steps in carrying out the slogan "Ikhlas Ruhnya Dakwah": internalization of the value of sincerity through spiritual regeneration, implementation of social da'wah without expecting anything in return, program selection based on the value of sincerity, leadership that exemplifies sincerity, evaluation based on intention rather than outward achievements, and maintenance of sincerity through dhikr and muhasabah. The urgency of developing the KPK's da'wah strategy is driven by socio-cultural changes in society, internal community challenges, the need to strengthen the implementation of the slogan's values, expansion into marginalized areas, and the professionalization of da'wah without losing its spiritual essence. The strengths of the KPK's strategy include an emphasis on spiritual values that distinguish it from commercial da'wah, a non-competitive and inclusive approach, spirituality-based cadre development, and flexibility in da'wah methods. Its weaknesses include the absence of objective measures to assess sincerity, high dependence on individual motivation, and a weak organizational management system, all of which lead to program inconsistency. The slogan "Ikhlas Ruhnya Dakwah" (Sincerity in Preaching) serves as the philosophical foundation guiding all of the KPK's preaching activities, ensuring they remain focused on the ultimate goal of pleasing Allah, without getting caught up in materialism or popularity. This study is expected to contribute to contemporary preaching strategies and serve as a reference for other preaching communities in developing strategies that are relevant, creative, and rooted in the value of sincerity.